1991
DOI: 10.1111/j.1471-6402.1991.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Client Preference for Counselor Gender

Abstract: This article presents the results of an investigation of male and female clients' expressed preferences for gender of their counselor. The study addressed two major comparisons: clients with a preference for therapist gender versus those without a preference, and clients with a preference for a male therapist versus those with a preference for a female therapist. LOGIT analyses indicate significant relationships among sex of the client, sex of the intake counselor, whether or not clients express a preference, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
1
12
0
2
Order By: Relevance
“…The finding that people generally prefer a female massage therapist may reflect the stereotypes by which we tend to think of women as more sensitive, caring, and nurturant than men, and parallels the finding that people generally prefer female therapists for talk therapies (Kaplan, 1996;Stamler et al, 1991), though in the case of massage there is probably more than just these stereotypes to be considered. In particular, the observations that men's preference for female massage therapists is very strong, while their comfort receiving massage from a man is often not very high, probably reflect socially reinforced sex roles related to touching.…”
Section: Massage Attitudes Pertaining To Sexuality and Gendermentioning
confidence: 55%
“…The finding that people generally prefer a female massage therapist may reflect the stereotypes by which we tend to think of women as more sensitive, caring, and nurturant than men, and parallels the finding that people generally prefer female therapists for talk therapies (Kaplan, 1996;Stamler et al, 1991), though in the case of massage there is probably more than just these stereotypes to be considered. In particular, the observations that men's preference for female massage therapists is very strong, while their comfort receiving massage from a man is often not very high, probably reflect socially reinforced sex roles related to touching.…”
Section: Massage Attitudes Pertaining To Sexuality and Gendermentioning
confidence: 55%
“…In an examination of clients' preferences among therapists of different sexes and gender-role orientations, McKinnon (1990) found that clients value both expressive and instrumental traits in descriptions of therapists, rating masculine men most highly, followed by androgynous women. Recent studies that indicate preferences for female therapists may mean that the prospective clients' definition of competence has expanded to include the value of empathy (Stamler et al, 1991). This may be especially true for female clients who were most likely to express a preference for the therapist by his or her sex and to express a preference for a female therapist (Stamler et al, 1991).…”
Section: Beliefs and Behaviors Of Clientsmentioning
confidence: 98%
“…Recent studies that indicate preferences for female therapists may mean that the prospective clients' definition of competence has expanded to include the value of empathy (Stamler et al, 1991). This may be especially true for female clients who were most likely to express a preference for the therapist by his or her sex and to express a preference for a female therapist (Stamler et al, 1991).…”
Section: Beliefs and Behaviors Of Clientsmentioning
confidence: 98%
See 2 more Smart Citations